2005
DOI: 10.1002/jor.20016
|View full text |Cite
|
Sign up to set email alerts
|

Altered knee kinematics in ACL‐deficient non‐copers: A comparison using dynamic MRI

Abstract: Kinematics measured during a short arc quadriceps knee extension exercise were compared in the knees of functionally unstable ACL-deficient patients, these patients' uninjured knees, and uninjured control subjects' knees. Cine phase contrast dynamic magnetic resonance imaging, in combination with a model-based tracking algorithm developed by the authors, was used to measure tibiofemoral kinematics as the subjects performed the active, supine posture knee extension exercise in the terminal 30 degrees of motion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 33 publications
1
38
0
1
Order By: Relevance
“…However, their work was unable to establish specific relationships between altered kinematics and the location of cartilage damage. Previous studies have suggested alteration of the joint contact point and pressure could contribute to cartilage degeneration after ACL injury and reconstruction [6,27,28,37]. These studies, however, have generally investigated only the path of tibial contact and have ignored the complex rolling and sliding components of the articular surface interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their work was unable to establish specific relationships between altered kinematics and the location of cartilage damage. Previous studies have suggested alteration of the joint contact point and pressure could contribute to cartilage degeneration after ACL injury and reconstruction [6,27,28,37]. These studies, however, have generally investigated only the path of tibial contact and have ignored the complex rolling and sliding components of the articular surface interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies exploring joint contact mechanics after ACL injury and reconstruction have focused on the tibial surface [6,27,28,37], though joint contact mechanics is defined between two articulating surfaces. Joint sliding distance, which compares femoral and tibial joint contact paths, was introduced as a kinematic surrogate for joint shear stress [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique has a number of disadvantages: (1) the impossibility of measuring the internal knee torques, limiting the understanding of the internal stress on the knee during a task that involves rotation 14,15 ; and (2) the movement of skin, fat, or muscle around the bone affects the marker position and can cause error in the analysis 16 . Other in vivo techniques, such as dynamic magnetic resonance imaging, computer-assisted navigation, and threedimensional radiostereometric analysis, are limited to environments too restrictive to perform high-demand activities [17][18][19] . According to Strobel and Stedtfeld 20 , functional tests are designed to reproduce the symptomatic subluxating process or to provoke an ''avoidance behavior'' to guard against subluxation, which likewise is interpreted as a positive sign.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using cadaveric knees (Bach & Hull, 1998;DeMorat et al, 2004;Renström et al, 1986) have shown that simulated quadriceps activity significantly increases ACL strain with the knee in up to 60° of flexion, and that ACL force peaks around 30° flexion (Li et al, 1999;Li et al, 2004). This was corroborated by in vivo studies, showing that actual quadriceps contraction causes ACL strain increases to 30° flexion (Beynnon et al, 1992), and that ACLdeficient knees show increased anterior translation on quadriceps contraction in the same range (Bach & Hull, 1998;Barrance et al, 2006;DeMorat et al, 2004). Studies examining the behaviour of the two bundles of the ACL on quadriceps contraction have shown equal band strain throughout flexion range (Bach & Hull, 1998;Wu et al, 2010).…”
Section: Quadriceps Loadmentioning
confidence: 87%